Membrane Dynamics in the Action of Dibutyryl Adenosine 3′:5′-Cyclic Monophosphate and Testosterone on Mammalian Cells - Puck, Theodore T. (1972)
The first manifestation of reverse transformation, in which a permanent epithelial-like cell is reversibly transformed into a fibroblast-like cell by dibutyryl adenosine cyclic 3′:5′-monophosphate, is the disappearance of a set of violently extending and retracting knobbed structures on the cell membrane with consequent tranquilization of the membrane. The cell then elongates to assume a fibroblast-like morphology. Permanently fibroblast-like cells, which have smooth membranes, can be changed into knobbed epithelial-like cells by the addition of either colcemid or cytochalasin B, agents that disorganize one or the other component, respectively, of the microtubular-microfibrillar system. Permanently smoothmembraned, epithelial-like cells also become knobbed by such treatment. All of these knobbed epithelial-like cells can be converted into smooth-membraned fibroblast-like cells by dibutyryl cAMP alone or with the aid of supporting molecules like testosterone. It is proposed that these are general phenomena and that the knobbed epithelial-like forms and the more highly differentiated smooth-membraned fibroblast-like cells represent extreme situations with respect to the degree of organization of the microtubular-microfibrillar system inside the cell.